Internacionalização de empresas e o fechamento do capital : um estudo sobre a deslistagem no mercado brasileiro - Santos, Murilo Alves (2016)
This work contributes to the finance literature proposing to analyze the relationship between the degree of internationalization of Brazilian companies and the likelihood of delisting. Therefore, even though the internationalization as a differential, in the formulation of hypotheses and analysis of the relationship between the variables dealt with concepts and theories within the Corporate Governance, which is already established in theory when it comes to delisting. First, with a view to the theory of internalization, which gives competitive advantages to the company due the adoption internationalization strategy and in parallel to the positive effects that this strategy generates on firms performance, it was formulated an hypothesis that the degree of internationalization would be adversely related to the probability of delisting, mainly due to such benefits generated to the organization. In turn, as an alternative hypothesis of the research, it proposed a positive relationship between these variables, based on agency theory, according to which internationalization would contribute to delisting by increasing geographical separation between shareholders and managers and, consequently, agency conflicts and the difficulty of monitoring. For the achievement of objectives, as well as being included economic and financial variables and GC, it was proposed the analysis of periods of crisis, as the events of recent past of the Brazilian economy. Starting from a base model initially developed by Pour and Lasfer (2013), which later, the proxies of internationalization and crisis have been added also contemplating adjustments to the Brazilian context. The data collected include the period from 2006 to 2014 and information on active and inactive companies at Bovespa. As results, it was found negative significance between the degree of internationalization and the delisting decision, confirming the first hypothesis of the research and stating that the benefits generated by internationalization in the company generate it spreads and results that reduce the probability of delisting. By analyzing the results of control variables was still possible to observe that, even internationalization reducing the likelihood of delisting, by particular aspects of corporate governance in Brazil, such as the high ownership concentration, the benefits it generates contribute to delisting. Regarding the analysis in crisis, the consequences of the crisis of the US subprime in general market were more relevant that the occurrence of itself, unlike the Brazilian internal crisis of 2014, which was statistically significant for the analyzed event. For future researches it is suggested the expansion of database and individual treatment of the reasons adopted by a company when delisting decision.